Balancing State, Market and Social Justice: Russian Experiences and Lessons to Learn - Avtonomov, Vladimir (Journal of business ethics, 2006)
This article deals with the relations in the triangle state–society–business in modern Russia. It is shown against Russian historical background, that the absolutist state in this country could never be identified with the society and these relations were shaped under its strong domination. The ethics of rule-following characteristic for market economy in general did not develop in Russia. The breakdown of communist Russia and market reforms proceeding since 1992 did not change this situation significantly. The period of political alliance between big business and government was followed by restoration of state dominance in somewhat modified forms. Both periods were characterized by corruption, which contrary to Putin’s slogans, increases in Russia. In the article I show the evolution of Putin administration’s policy which changed from emphasizing and improving legal institutions to selective use of legal norms depending on personal loyalty. Main forms of state exploitation of Russian business are described. The conclusion is that Russian experience of balancing state and market should be called negative.